TREATMENT OF PEDIATRIC OBSESSIVE COMPULSIVE DISORDER UTILIZING PARENT‐FACILITATED ACCEPTANCE AND COMMITMENT THERAPY. Issue 1 (January 2017) - Barney, Jennifer Y.; Field, Clint E.; Morrison, Kate L.; Twohig, Michael P.
Abstract : Acceptance and commitment therapy (ACT) is a modern form of cognitive behavior therapy that uses acceptance and mindfulness‐based procedures to address clinical issues. A brief protocol of ACT was used with 3 children ages 10 and 11 years who were diagnosed with obsessive compulsive disorder (OCD). Results showed notable and clinically significant reductions of OCD across participants. These findings are noteworthy because the treatment was provided by a school psychologist, it is the first application of ACT for pediatric OCD, and it is one of a few studies using ACT with children. Limitations and future directions are discussed.